A Novel Chaos-Based Image Encryption Scheme by Using Randomly DNA Encode and Plaintext Related Permutation - Zhen Li; Changgen Peng; Weijie Tan; Liangrong Li (Applied Sciences, 2020)
To ensure the security and privacy of digital image when its transmitting online or storing in the cloud, we proposed a novel chaos based image encryption scheme by using randomly DNA encode and plaintext related permutation. In our scheme, we first randomly encode plain image into a nucleotide sequence under the control by the piecewise linear chaotic map(PWLCM). After that, the plaintext related permutation would be done under the control sequence which generated by hyper chaotic Lorenz system (HCLS). Next, we make diffusion processing with key DNA sequence which is generated by another PWLCM system and also encoded randomly. Finally, we decode DNA sequence into cipher image matrix. In addition, we used many common security analysis methods to test our scheme, and the result compared with other works. The tests and comparison results are shown that our proposed image cryptosystem has excellent security performance to ensure the digital image security on communication.